Seamless Retail in Emerging Market: a Transaction-Based Analysis of Omnichannel Customer Experience at Bhinneka.com - Dennis Kumara; Elke Alexandrina (School of Business, IPB University (SB-IPB), 2026)
Background: Advances in digital technology have changed the way consumers interact with retail brands, encouraging a shift toward integrated shopping experiences across online and offline channels. In Indonesia, empirical studies that explore omnichannel strategies from an internal organizational perspective are still limited. This limitation creates a gap in understanding how omnichannel strategies are implemented at the firm level and how real behavioral data can support better strategic decisions.Purpose: This study examines omnichannel customer experience in the context of Indonesian e-commerce, focusing on how customers actually move across digital and physical touchpoints during their purchase journey. Most existing studies rely on survey data from developed markets, whereas this study fills that gap by using real transaction records from Bhinneka.Com, one of Indonesia's pioneering multi-category e-commerce platforms.Design/methodology/approach: A descriptive quantitative case study design was employed, using internal transaction data from Bhinneka.Com collected throughout 2018 (Q3 2018 – Q4 2018: approximately 16.6 million sessions per quarter). Consumer behavior was analyzed across seven indicators: acquisition metrics, engagement, conversion funnel, product category performance, purchase cycle transitions, campaign effectiveness, and customer segmentation. Analytical techniques included funnel conversion analysis, transition rate analysis, and category-based comparison.Findings/Result: Findings reveal significant friction in the customer journey: bounce rates ranged from 25% to over 61% across quarters, while the checkout stage recorded a cart abandonment rate of 82.44%. Automated email campaigns, particularly abandoned cart reminders, achieved open rates of up to 37.2%, but conversion remained below 1%. Only 40% of first-time buyers completed a second purchase, confirming that the first to second purchase transition is the most critical retention bottleneck.Conclusion: Theoretically, this study extends omnichannel consumer behavior research by providing transaction level behavioral evidence from an emerging market. Practically, the findings show that reducing checkout friction, improving post-first-purchase engagement, and building personalization depth in automated campaigns are the most commercially impactful priorities for Indonesian ecommerce retailers.Originality/value (State of the art): This study provides practical insights based on internal transaction data, offering a data-driven contribution to omnichannel research in the context of Indonesia’s retail industry. Keywords: omnichannel strategy, consumer behavior, ecommerce retailers, e-commerce, Indonesia